Zootechnical Additives for Optimum Production in Livestocks in Stallfed Condition - Singh, Naveen Kumar; Singh, Alok; Singh, S.V.; Singh, J.P.; Jaiswal, Sonu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This is the point of interest to use zootechnical additives in ruminants to control the accumulation of lactate in the rumen. The primary and main cause of acidosis is due to consumption of rapidly digestible carbohydrate in high amount. In normal animal husbandry (stall fed) practices generally livestock are feed with the left out or waste products rich in carbohydrates. This excessive carbohydrate consumption leads to sudden change in ruminal environment, causing sub-acute or chronic lactic acidosis. The ruminal lactic acidosis problem can be averted by either zootechnic additives such as Saccharomyces cereviseae and Megasphaera elsdenii or adding sodium bicarbonate/enzymes in feed or ration.